Ritual Treats in Russian Wedding Ceremonies in Udmurtia - S. V. Tolkachova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article is devoted to the analysis of ritual treats in Russian wedding ceremonies in southern and central regions of modern Udmurtia. Based on the study of field materials collected by the author in folklore expeditions in the territory of Udmurtia and published sources of researchers of Russian folklore of Udmurtia, the etiquette of treats in a traditional wedding ceremony is considered. It is indicated that the features of ritual treats are reflected in the names of some wedding episodes. A review of the codes of the ritual involved in the wedding feasts is made. The types of the use of ritual drinks in the wedding ceremony are considered. The descriptions of the meals at the wedding table in the bride’s house are given. The tradition of drinking the “wedding” wine is considered. The study reveals that praying, groomsman’s sayings, singing of velichaniya and wedding songs, some kinetic acts - bypassing a table, tipping over glasses, throwing coins in the water, dancing with kurnik - served as a consecration of the food. The fragments of the wedding ritual, in which the numerical symbolism is clearly shown, are characterized. Special attention is paid to the symbolism of the wedding table. There are semantic connections between the wedding table and the bride. The question is raised about the role of woven items - scarves, tablecloths, handkerchiefs, sheets - in the design of wedding feasts. Typological similarities of ritual food in the Russian, Udmurt and Besermyan traditional cultures are revealed.